Efisiensi Administrasi Persuratan melalui Simodis Berbasis Design Thingking pada Dinas Pekerjaan Umum Kota Semarang - Fadia Puspita Maharani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research was conducted at the Semarang City Public Works Department, particularly in the secretariat section responsible for correspondence administration and public information management (PPID). The study focuses on the conventional management of letter disposition, which makes it difficult for PPID officers to monitor letter status quickly, reduces process transparency, and may cause delays in decision-making and public services. This research aims to develop and implement a Disposition Monitoring Information System (SIMODIS) to digitize correspondence administration so that it becomes more effective, efficient, transparent, and accountable. The study uses ASTRID Analysis to identify strategic issues and a Design Thinking approach consisting of the Empathize, Define, Ideate, and Prototype stages. Empathy Map and Persona were also used to understand user needs. System testing was conducted using Black Box Testing to assess functionality and the System Usability Scale (SUS) to evaluate user experience. The results show that SIMODIS was successfully developed with features such as an admin dashboard, digital disposition forms, and a public mail status search portal. The SUS score reached 83, categorized as Excellent, indicating high usability and user acceptance.